Hafnia Nanodots: Multi‐"Color" Delineation of Bone Microdamages Using Ligand‐Directed Sub‐5 nm Hafnia Nanodots and Photon Counting CT Imaging (Adv. Funct. Mater. 4/2020). (24th January 2020) - Ostadhossein, Fatemeh; Tripathi, Indu; Benig, Lily; LoBato, Denae; Moghiseh, Mahdieh; Lowe, Chiara; Raja, Aamir; Butler, Anthony; Panta, Raj; Anjomrouz, Marzieh; Chernoglazov, Alex; Pan, Dipanjan
Abstract : Bone as a functional material could experience various stresses that could lead to microdamages. In article number 1904936, Dipanjan Pan and co‐workers show that targeted hafnia nanoparticles and photon counting spectral computed tomography can detect microdamages. This advanced technology could determine signals from hafnia nanoparticles bound to the hard tissue of bone both in the ex vivo model and in vivo.